REVIEW OF THE INTRODUCTION AND AUDIT OF THE USE OF THE ACUTE RESUSCITATION PLAN AND RELATED DOCUMENTS TO ENHANCE END-OF-LIFE CARE ACROSS THE TOWNSVILLE HOSPITAL, A LARGE TERTIARY HOSPITAL IN PROVINCIAL QUEENSLAND. Issue 2 (1st June 2013) - Cairns, W; Maluga, Y; Lane, P; Aitken, P; Howe, D
Abstract : Background: Historically many of the medical orders concerning end-of-life (E-o-L) care and ' not for resuscitation ' (NFR) were inadequate as they did not include evidence of the decision making process or the wishes and capacity of the patient. The introduction in Queensland of the Advance Health Directive and Enduring Power of Attorney (AHD and EPOA)(1998) and the Acute Resuscitation Plan (ARP) (2009)—and the Paediatric ARP (PARP)(2012) – has changed the care delivered to dying patients. Aim: To review the impact of the introduction of the use of the ARP and the PARP across The Townsville Hospital, a tertiary hospital in provincial Queensland. Methods: The use of the ARP or satisfactory equivalent documentation was audited in the medical records of all people who died in The Townsville Hospital over 3 months from 1 January 2013 to 31 March 2013. Staff from across the hospital, including the MET service, were interviewed to ascertain their opinions on the impact of the introduction of these documents. Results: Preliminary results from a limited QA audit in 2012 indicate that about 80% of dying patients had a resuscitation plan in place when they died. Clinicians are very positive about the benefits. Conclusion: The response of clinicians indicates that care has been improved by the ARP with patients' wishes being respected. The quantitative data are likely to confirm this. The introduction of these forms across the hospital has contributed to a changed culture of health care to the benefit of patients, their families and clinicians.